Faktor Penentu Keputusan Mengikuti Pelatihan Daring pada Wanita Pemilik Kartu Prakerja - Farah Putri Wenang Lusianingrum; Lina Affifatusholihah; Soletahin Ika Putri (Politeknik Negeri Bengkalis, 2020)
There are currently eight digital platform partners for conducting online training. The digital platform partner of the Prakerja Card provides 1,338 types of training from business to personal development. Furthermore, there are still five digital platforms that submit proposals to be able to join as partners in the Prakerja Card Program and there are 362 new types of training proposed by partners. With the increasing number of choices for the type of training, the partner anda organizers need to evaluate the factors determining the decision to take part in online training for women who have Prakerja Cards in Banten Province. The research approach used is quantitative. The population of this research is women who have Prakerja Card in Banten Province. The number of respondents in the study was 150 obtained by purposive sampling method. SEM Warp PLS application is used for statistical data computation. The results revealed that the factors that could influence the decision to participate in training for women who have Prakerja Card in Banten Province were cultural, social, personal, and technological factors.